Influences of fatigue and anticipation on female soccer players’ biomechanical characteristics during 180° pivot turn: implication for risk and prevention of anterior cruciate ligament injury - Zou, Limin; Zhang, Xiaochun; Jiang, Ziang; Wu, Xie; Zhang, Qiang (Frontiers in Physiology, 2024)
Introduction Athletes’ capability to perform activities with body rotation could be weakened by fatigue accumulation. Making pivot turning in unanticipated scenarios after fatigue may greatly challenge athletes’ ability to adapt rational motion strategies, elevating the risk of anterior cruciate ligament (ACL) injury. This study aimed to investigate the effects of fatigue and anticipation on biomechanical risk factors of ACL injury during 180° pivot turns in female soccer players. Methods Twenty-one female soccer players were selected as participants. The participants performed anticipated turning maneuver before the fatigue intervention. The participants sprinted along the runway, decelerated and planted their foot on the force plate, and then executed a 180° pivot turn. For unanticipated tests, the pivot turn was mixed with side/cross-cuts, which were indicated to the participant using a custom-designed light system. The tests were repeated by the participant after receiving a fatigue intervention. Lower-limb joint angles and moments were characterized. Peak ground reaction forces (GRFs) and GRF loading rates were determined. Two-way repeated measures analysis of variance was applied to examine the effects of fatigue and anticipation on the variables of interest. Results Compared to the anticipated conditions, the approach speed was significantly lower in the unanticipated tests (P < 0.0001). Lower-limb kinematics showed varied angular patterns across conditions: greater hip joint variations in flexion, abduction, and internal rotation during unanticipated turns; consistent knee joint flexion and ankle plantarflexion with dorsiflexion observed mid-turn. Significant interactions (P = 0.023 to P = 0.035) between fatigue and anticipation influenced hip joint angles. Anticipation effects were notable at initial contact and peak ground reaction force, increasing hip, knee, and ankle joint angles (P < 0.0001 to P = 0.012). Participants showed consistent ground reaction force (GRF) patterns during pivot turns across fatigue and anticipation conditions, with the first peak occurring approximately 10% into the turn period. Significant interaction effects (P = 0.016) between fatigue and anticipation were observed for knee flex/extension moments at the first peak vertical GRF. Anticipation significantly increased first peak vertical (P < 0.0001), anteroposterior (P < 0.0001), and mediolateral (P < 0.0001) GRFs. Fatigue increased first peak vertical (P = 0.022), anteroposterior (P = 0.018), and mediolateral (P = 0.019) GRFs. Post-fatigue, participants exhibited reduced first peak GRFs and loading rates compared to pre-fatigue conditions, with higher rates observed in unanticipated turns (vertical GRF: P = 0.030; anteroposterior GRF: P < 0.0001). Conclusion Female soccer players’ lower-limb Biomechanical characterization could be greatly affected by the change of anticipatory scenarios. With the associated increase of GRF, the risk of their ACL injury might be elevated. Fatigue affected female soccer players’ abilities on movement performances, but the interaction of these two factors could potentially weaken their knee’s functions during pivot turns. Cognitive training on unanticipated tasks may be important for rehabilitation training after ACL injury.